Epidemiology of animal poisoning: An overview on the features and spatio-temporal distribution of the phenomenon in the north-eastern Italian regions. (September 2016) - Bille, Laura; Toson, Marica; Mulatti, Paolo; Dalla Pozza, Manuela; Capolongo, Francesca; Casarotto, Claudia; Ferrè, Nicola; Angeletti, Roberto; Gallocchio, Federica; Binato, Giovanni
Highlights: Suspected animal poisonings and baits recovery cases submitted between 2007 and 2013 were analyzed. Toxic agents were verified in 35% of animal poisoning cases and in 42% of suspected baits. Dogs and cats were the most severely affected species. The main toxicants identified were carbamates in animal poisoning and anticoagulants in baits. Hotspots were identified in highly urbanized areas. Abstract: In the present paper we analyze and discuss about the records referring to animal poisonings and poisoned baits cases covering the period between 2007 and 2013 and submitted for diagnostic investigations to the Istituto Zooprofilattico Sperimentale delle Venezie (IZSVe), which is the public veterinary health institute competent for the north eastern Italian regions. All data were gathered by a passive surveillance system based on voluntary reporting, which became mandatory in 2009 after a decree of the Italian Ministry of Health had come into force. This prohibited the use and detention of poisoned baits and ordered to selected institutions and professionals to carry out standardized surveys to assess suspect and/or confirmed reported cases; all the necessary anatomopathological and toxicological investigations to confirm the reported cases were then performed for free by public veterinary health institutes whenever a veterinarian diagnosis or clinical suspicion were provided. Totally, 1831 suspected animals poisoning and 698 cases of supposed poisoned baits recovery episodes were registered. 642/1831 (35.1%) animal poisoning cases were confirmed and the presence of toxic agents was verified in 292/698 baits (41.8%). The most severely affected territories were the ones with the highest level of urbanization and those most densely populated in the study area. Dogs and cats seemed to be greatly affected by poisoning cases and a characteristic seasonal trend was noticed, with an increase of episodes in late Winter/early Spring and in Autumn. Carbamate insecticides resulted to be the main cause for animal poisoning, while anticoagulants rodenticides played a primary role among toxicants found in poisoned baits. The presented results emphasize that malicious animal poisoning is a widespread problem in north-eastern Italy. The still relevant number of reported poisoning events caused by some banned pesticides poses the problem of identifying where these substances come from and brings to light the popular knowledge about the high toxicity of these compounds. Moreover, the noticeable increase of the number of episodes registered in 2009 pointed out how the above mentioned decree may have contributed to reveal a number of hidden cases which had not been investigated before, probably due to economic reasons related to the costs of toxicological analyses.